أثر الالتزام بتطبيق المعايير البيئية في الصناعات الكيميائية في سورية (الشركة العامة لصناعة الأسمدة نموذجاً) - محمود, حبيب; تفاحة, أيهم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر الأنشطة الصناعية مصدراً من المصادر الرئيسية التي تؤثر على سلامة البيئة، وذلك عن طريق إفراز ملوثات صناعية، سواء أكانت غازية أم سائلة أم صلبة، ولا يمكن اعتبار جودة الصناعات دون التحكم البيئي من خلال الالتزام بتطبيق المعايير البيئية، وإيجاد الحلول للمخاطر والمشكلات البيئية للصناعات، وبالأخص الصناعات الكيميائية التي تعد من أكثر الصناعات تلويثاً للبيئة وأكثرها أهمية من الناحية الاقتصادية، لأن المواد الكيميائية موجودة وتستخدم إما بشكل مباشر أو تعد كمواد خام ضرورية للتصنيع في الصناعات الأخرى. وبسبب تعاظم المشكلات البيئية وانعكاساتها الاقتصادية والاجتماعية في عالم اليوم، فإن الجدل يتركز بشكل أساسي من خلال: أثر النمو الصناعي على سلامة البيئة، وأثر الالتزام بتطبيق المعايير البيئية على النمو الصناعي. إن جوهر قضايا البيئة ذات الصلة بالصناعة هو كيفية تحقيق توازن بين الحاجة إلى النمو الصناعي وبين الحاجة إلى الحفاظ على البيئة، والذي يأتي من خلال رسم سياسات صناعية تراعي البعد البيئي وتحقق التنمية الصناعية المتوازنة. ونظراً لأهمية وحيوية الموضوع جاء هذا البحث ليسلط الضوء على أهمية دراسة أثر الالتزام بتطبيق المعايير البيئية في الصناعات الكيميائية باعتبارها من الصناعات المهمة في سورية، وبالتحديد دراسة أثر الالتزام بتطبيق المعايير البيئية في الشركة العامة لصناعة الأسمدة ، باعتبارها من الصناعات المهمة اقتصادياً وأكثرها تلويثاً للبيئة، في سبيل الوصول إلى صناعة متطورة وصديقة للبيئة في سورية. The industrial activities are considered one of the main sources that affect the safety of the environment, through the secretion of industrial pollutants, whether gas or liquid or solid, and the quality of industries cannot be considered without environmental control through a commitment to the application of environmental standards, and to find solutions to the risks and environmental problems in the industry, and in particular the chemical industry which is one of the industries that mostly pollutes the environment and the most important industry economically. This is because chemicals are used either directly or as raw materials which are necessary for manufacturing in other industries. Because of the growing of environmental problems and their implications for economic and social development in today's world, the debate is centered primarily through: the impact of industrial growth for the safety of the environment, and the impact of the obligation to apply environmental standards on industrial growth. The essence of the environmental issues related to industry is how to achieve a balance between the need for industrial growth and the need to conserve the environment, and that comes through the design of industrial policies that take into account the environmental dimension and achieving balanced industrial development. Given the importance and vitality of the topic, this research attempts to highlight the importance of studying the impact of the obligation to apply environmental standards in the chemical industry as one of the important industries in Syria, specifically studying the impact of the obligation to apply environmental standards at the General Company for the Fertilizer Industry, since industries are economically important and the most polluting for the environment. This is to reach an advanced and industry-friendly environment in Syria.